Development of Smart Trash Bins (RoboBin) in Tourist Areas - Zakaria, Normah; Norhasyimah,; Arihasnida,; Siti Nur Kamariah, (Research and Innovation in Technical and Vocational Education and Training, 2023)
This project is about designing and developing a tool that can create a cleaning service in a certain place. The project built is a smart trash can named 'RoboBin'. Trash cans are one of the most important assets for users to ensure that every area is clean. As we know, this trash can is indeed a place where people throw unused materials into it. Without this asset, it is difficult for the community to dispose of this waste and resulting in the phenomenon of littering everywhere. In relation to that, other people's views will fall and cause them to lose focus on visiting the area. Tourist places are the focus of many people visiting and the cleanliness aspect needs to be taken care of in order to provide comfort to all parties whether residents, tourists, owners of tourist areas, and the government. This built project uses a microcontroller that is equipped with several detectors such as ultrasonic sensors, motion sensors, and infrared sensors and is further programmed through the integrated circuit concept to move and stop to give the user time to throw the trash into it and detect the level of trash stored in RoboBin. For this stopping process, it uses a motion sensor where it detects the movement of the hand in the area that has been marked on the top of the RoboBin and then it will stop to give time for the user to throw the trash into it. Overall, this project can be used for the convenience of users.